Desde la Amazonía peruana: aportes para la formación docente en la especialidad de educación inicial intercultural bilingüe - Trapnell, Lucy (2011)
From the Peruvian Amazon: Contributions for teacher training in intercultural bilingual early childhood educationThe promotion of universal access to early childhood education should be accompanied by a serious analysis and reflection on the impact it can have on the primary socialization of native children. In this context it is essential to guarantee the existence of teacher training programs conscious of the relation between apprenticeship and culture which offer their students inputs that allow them to value, complement and enrich the educational processes which occur at home and in community settings. This paper presents some core issues of two curricula developed by and for Amazonian indigenous peoples. Even though both guidelines have been designed in Amazonian contexts, and respond to the needs and demands of Amazonian indigenous organizations, the topics included in this document may be used as referents for the critical examination of the way in which early childhood teacher training in intercultural bilingual education is being approached in other contexts.